2002
DOI: 10.1007/s00216-001-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of neurotoxic insecticides in food using disposable acetylcholinesterase-biosensors and simple solvent extraction

Abstract: The extensive use of pesticides to protect agricultural crops necessitates reliable tools for the detection of residues in food and water, thus ensuring environmental protection and consumer safety. Neuroinhibitors such as organophosphates and carbamates in particular, represent a potential hazard to human health. These compounds are frequently found in food but conventional methods of analysis are limited as they are either time consuming or not sufficiently sensitive. As a result, a rapid and sensitive biose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 20 publications
(37 reference statements)
2
42
0
Order By: Relevance
“…Generally the amount of organic solvent should be not higher than 5%, as also reported by Pohanka et al, suggesting that convenient solvents were propan-1,2-diol and isopropanol [71]. An interesting approach was reported by Arduini et al [164] and Schulze et al [165]. They demonstrated that organic solvents, which are completely insoluble in aqueous phase, such as hexane or octanol in the first case, or octanol in the second case, caused only a marginal reduction of enzyme activity (less than 5%) and can be used for the extraction and measurement of insecticides without effect on enzyme activity.…”
Section: Measurement Of Insecticides and Nerve Agents In Presence Of mentioning
confidence: 84%
See 1 more Smart Citation
“…Generally the amount of organic solvent should be not higher than 5%, as also reported by Pohanka et al, suggesting that convenient solvents were propan-1,2-diol and isopropanol [71]. An interesting approach was reported by Arduini et al [164] and Schulze et al [165]. They demonstrated that organic solvents, which are completely insoluble in aqueous phase, such as hexane or octanol in the first case, or octanol in the second case, caused only a marginal reduction of enzyme activity (less than 5%) and can be used for the extraction and measurement of insecticides without effect on enzyme activity.…”
Section: Measurement Of Insecticides and Nerve Agents In Presence Of mentioning
confidence: 84%
“…The organophosphorus and carbammic insecticides were also measured in extract of sheep wool [183], potable, river and lake water samples [47, 133,184], milk [185], grape and vine leaf samples [186,187], wheat and durum wheat [188][189][190], apple skin [191], orange juice [165], garlic [192], lettuce, rice, onion [193,194], in samples of fruit, vegetable and dairy product [48,195] and directly in tomato [196]. In the last case, the insecticides were measured without any previous manipulation of the sample, in fact the biosensor was immersed directly in the tomato pulp obtaining a recovery of 83.4% and showing a very low interference of the matrix components.…”
Section: Cholinesterase Biosensor Applications For Nerve Agents Measumentioning
confidence: 99%
“…These matrix particles could not be removed from the electrode surface by washing it with either buffer or water. One possibility to prevent these matrix effects is to add an extraction step in the protocol followed by incubation in the solvent extract, as described by Schulze and coworkers (Schulze et al, 2002). In the present study, matrix effects were avoided by treating the electrodes with a 1 vol-% Tween-20 solution in phosphate-buffer (pH 7,5) after their incubation in the food samples.…”
Section: Preventing Matrix Effects With Electrode Modificationmentioning
confidence: 97%
“…Therefore, it is important to determine the levels of OPs in vegetables to protect human health (de Silva et al, 2006;Uygun et al, 2007;Darko and Akoto, 2008;Zhao and Zhao, 2009 analyses, they are generally time-consuming, expensive, labor-intensive, and use relatively large volumes of solvents. Recently, the acetylcholinesterase inhibition method has been successfully applied to the determination of OPs in various environmental matrices (Schulze et al, 2002). In most cases, the acetylcholinesterase applied in this method is extracted from the head of the fly Musca domestica.…”
Section: Introductionmentioning
confidence: 99%